Race/ethnicity and underlying disease influences hematopoietic stem/progenitor cell mobilization response: A single center experience. Issue 4 (28th May 2021) - Uzoka, Chukwuemeka; Liu, Li C.; Park, Youngmin; Lin, Yuankai; Patel, Pritesh; Campbell‐Lee, Sally; Sweiss, Karen; Wang, Xinhe; Tepak, Elena; Peace, David; Saraf, Santosh; Rondelli, Damiano; et al.
Abstract: Background: Whether race/ethnicity plays a role in hematopoietic stem/progenitor cells (HSPC) mobilization in autologous donors has not been studied. We hypothesize that donor characteristic including race/ethnicity, age, sex, body mass index, and diagnostic groups influences HSPC mobilization. Diagnostic groups include healthy allogeneic donors, autologous multiple myeloma (MM) and non‐MM donors. Study Design and Methods: Here, we conducted a single‐center retrospective study in 64 autologous patients and 48 allogeneic donors. Autologous donors were patients diagnosed with MM or non‐MM. All donors were grouped as African American (AA), White (W), or "Other"(O). Results: Multivariate analysis demonstrated diagnostic group differences for CD34+ cell yields between race/ethnicity. Specifically, non‐MM patients had the lowest CD34+ cell yields in AA and O, but not in W. For pre‐apheresis peripheral blood (PB) CD34+ cell numbers, race/ethnicity had a significant effect both in bivariate and multivariate analyses. Non‐MM patients had the lowest, and AA patients had the highest PB CD34+ cells. The results support the view that past therapies used in MM are likely more conducive of recovery of HSPC. Conclusions: Our study shows that race/ethnicity and diagnostic group differences influenced CD34+ cell mobilization response across donor types. Interestingly, autologous MM donors with the aid of plerixafor displayed comparable CD34 yields to allogeneic donors. Even though both MM and non‐MM donors received plerixafor, non‐MM donors had significantly lower CD34 yields among AA and O donors but not in W donors. Larger studies would be required to validate the role of diagnostic groups and race/ethnicity interactions.